Biodiesel Production Via Heterogeneous Transesterification Of Palm Olein And Waste Oils - Maniam, Gaanty Pragas (2011)
In the present work, attempts have been made to use calcium oxide (CaO) as a heterogeneous catalyst in the transesterification of triglycerides with methanol to produce methyl esters (biodiesel) as the main product. Laboratory CaO as well as waste CaO from the shells of crabs (Scylla serrata) and cockles (Anadara granosa) have been successfully utilized as catalysts to transesterify palm olein as well as waste adsorbed oil from SBC and chicken oil. In order to enhance the catalytic activity, the catalysts have to be calcined at 900 °C for 2 h. Upon calcination the catalysts transformed to CaO from the initial CaCO3 structure.